Effects of nucleation pretreatment on corrosion resistance of conversion coating on magnesium alloy Mg-10Gd-3Y-0.4Zr - Chunyan Zhang; Yuyang Chen; Baoxing Yu; Peng Zhou; Yunfei Zhai; Yan Chen; Xiaochen Zhang; Tao Zhang; Fuhui Wang (Corrosion Communications, 2023)
To improve corrosion resistance of phosphate chemical conversion coatings (PCCs) on magnesium alloy Mg-10Gd-3Y-0.4Zr, a new route was proposed. The phosphate conversion treatment was preceded by two nucleation pretreatment processes in the form of physical adhesion and chemical adsorption. The present study focused on the effects of two nucleation pretreatments of silane coupling agent KH-550 + nano-SiO2 sol process and Ti/Zr surface modification treatment on microstructure and corrosion resistance of PCCs on magnesium alloy Mg-10Gd-3Y-0.4Zr. Results demonstrate that nucleation pretreatment can prefabricate dispersed nuclei on substrate's surface, which significantly enhances the nucleation rate during the initial stage of coating formation, and decreases the crystal size of PCCs. Corrosion resistance of the PPCs was increased by a factor of 4. The Ti/Zr pretreatment demonstrates a superior application perspective due to the ease-of-fabrication and simplicity.